2003
DOI: 10.1128/jb.185.1.126-134.2003
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ion Dependence of RecombinantEscherichia coliAllantoinase

Abstract: Allantoinase is a suspected dinuclear metalloenzyme that catalyzes the hydrolytic cleavage of the fivemember ring of allantoin (5-ureidohydantoin) to form allantoic acid. Recombinant Escherichia coli allantoinase purified from overproducing cultures amended with 2.5 mM zinc, 1 mM cobalt, or 1 mM nickel ions was found to possess ϳ1. Absorbance spectroscopy of the cobalt species reveals a band centered at 570 nm consistent with five-coordinate geometry. Dithiothreitol is a competitive inhibitor of the enzyme, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 56 publications
(63 reference statements)
1
33
0
Order By: Relevance
“…Note that, for functional analysis, the enzyme was expressed in the presence of zinc (Supplementary Data). 21 Mutation of Asn94 and Ser317, as well as the metal-ligating residue Asp315, completely abolished enzyme activity, and nonamended allantoinase, which was grown in the absence of supplemental zinc, remained inactive. In contrast, mutations at Arg215 and Ser288 did not exert significant effects on enzyme activity.…”
Section: D-hydantoinase [Protein Datamentioning
confidence: 98%
See 1 more Smart Citation
“…Note that, for functional analysis, the enzyme was expressed in the presence of zinc (Supplementary Data). 21 Mutation of Asn94 and Ser317, as well as the metal-ligating residue Asp315, completely abolished enzyme activity, and nonamended allantoinase, which was grown in the absence of supplemental zinc, remained inactive. In contrast, mutations at Arg215 and Ser288 did not exert significant effects on enzyme activity.…”
Section: D-hydantoinase [Protein Datamentioning
confidence: 98%
“…6 Biochemical studies using E. coli allantoinase have demonstrated that its activity depends on the presence and type of metal in the active center, analogous to other enzymes in this family. 20,21 Contrary to these observations, a metal-independent allantoinase (puuE) was recently characterized structurally and functionally from Pseudomonas fluorescens, in which allantoin was known to be used as a nitrogen source, even in the absence of gene for the metal-dependent allantoinase. 22 This new type of allantoinase was initially annotated as a polysaccharide deacetylase and has no sequence homology with the metal-dependent enzyme.…”
mentioning
confidence: 94%
“…5, asterisks) responsible for metal biding were found in all reported ALNs. Recently, the recombinant E. coli ALN was shown to have the highest activity levels when observed in cell extracts from cultures supplemented with zinc and cobalt (Mulrooney and Hausinger, 2003).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…The ion present in the enzyme is most likely to be manganese since it is the only cation that restored the activity in both enzymes, and cobalt has a predicted low bioavailability. The reconstitution of an enzyme in vitro by an ion different to that present in vivo is possible; cobalt is able to substitute other ions such as zinc (Mulrooney and Hausinger 2003) and manganese (Carvajal et al 1996). The effect of manganese is shared by other ureidoglycolate-degrading enzymes, such as ureidoglycolate urea-lyases from fish (Takada and Noguchi 1986) and microorganisms (Trijbels and Vogels 1967;Takada and Tsukiji 1987) and allantoicase from C. reinhardtii (Piedras and Pineda 2003).…”
Section: Discussionmentioning
confidence: 96%